Developing thinking skills and attitude among second year students using a module in the concept heritage - Alcantara, Consuelo Wenceslao 1937- (1977)
The purpose of the study was to know how a module on the concept "Heritage" in the second year Social Studies may be constructed in order to develop thinking skills and attitudes. The study was limited only to the preparation of an instructional module on the concept of Heritage for second year high school Social Studies specifically for use at the Don Mariano Marcos State College. It also discussed how modules can be developed to enable students to acquire knowledge, develop thinking skills, and form desirable attitudes. The instructional module is a self-contained instructional unit which can bring about learning with minimum teacher direction. It contains the basic elements of instruction-objectives, learning activity and evaluation.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Secondary) -- Philippines -- Bacnotan (La Union); Individualized instruction -- Philippines -- Bacnotan (La Union); Teaching -- Philippines -- Bacnotan (La Union) -- Aids and devices; Thought and thinking